Alternative Scenarios for Improving the Efficiency of the Product Quality Management Mechanism (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article discusses alternative scenarios for increasing the effectiveness of the product quality management mechanism at local textile enterprises located in the republic, in particular, at enterprises in the Andijan region.